Dampening the DAMPs: How Plants Maintain the Homeostasis of Cell Wall Molecular Patterns and Avoid Hyper-Immunity - Pontiggia, Daniela; Benedetti, Manuel; Costantini, Sara; De Lorenzo, Giulia; Cervone, Felice (Frontiers in Plant Science, 2020)
SSeveral oligosaccharide fragments derived from plant cell walls activate plant immunity and behave as typical damage-associated molecular patterns (DAMPs). Some of them also behave as negative regulators of growth and development, and due to their antithetic effect on immunity and growth, their concentrations, activity, time of formation, and localization is critical for the so-called “growth-defense trade-off”. Moreover, like in animals, over accumulation of DAMPs in plants provokes deleterious physiological effects and may cause hyper-immunity if the cellular mechanisms controlling their homeostasis fail. Recently, a mechanism has been discovered that controls the activity of two well-known plant DAMPs, oligogalacturonides (OGs), released upon hydrolysis of homogalacturonan, and cellodextrins (CDs), products of cellulose breakdown. The potential homeostatic mechanism involves specific oxidases belonging to the family of berberine bridge enzyme-like (BBE-like) proteins. Oxidation of OGs and CDs not only inactivates their DAMP activity, but also makes them a significantly less desirable food source for microbial pathogens. The evidence that oxidation and inactivation of OGs and CDs may be a general strategy of plants for controlling the homeostasis of DAMPs is discussed. The possibility exists of discovering additional oxidative and/or inactivating enzymes targeting other DAMP molecules both in the plant and in animal kingdoms.